The impact of flash glucose monitoring on glycated hemoglobin in type 2 diabetes managed with basal insulin in Canada: A retrospective real-world chart review study. (July 2021) - Elliott, Tom; Beca, Sorin; Beharry, Rajendra; Tsoukas, Michael A; Zarruk, Alexandro; Abitbol, Alexander
Background: The real-world effect of intermittently scanned continuous glucose monitoring on glucose control in type 2 diabetes treated with basal insulin is uncertain. This retrospective real-world study aimed to evaluate change in glycated hemoglobin (HbA1c) amongst adults with type 2 diabetes managed with basal insulin starting flash glucose monitoring. Methods: Medical records were reviewed for adults with type 2 diabetes treated with basal insulin for ⩾1 year and using FreeStyle Libre TM Flash Glucose Monitoring for ⩾3 months. Prior to device use an HbA1c 8.0%–12.0% was recorded and a further HbA1c result was recorded 3–6 months (90–194 days) after starting device use. Results: Medical records ( n = 91) analyzed from six Canadian diabetes centers showed HbA1c significantly decreased by 0.8% ± 1.1 (mean ± SD, [ p < 0.0001]) from mean baseline HbA1c 8.9% ± 0.9 to 8.1% ± 1.0 at 3–6 months after initiating flash glucose monitoring. HbA1c improvement was not independently associated with age, BMI, insulin use duration, or sex. Conclusion: This Canadian real-world retrospective study showed significantly reduced HbA1c following initiation of ﬂash glucose monitoring technology to further support management of type 2 diabetes treated with basal insulin.